INVITRO ANTIBACTERIAL ACTIVITY OF METHANOLIC LEAF EXTRACT DERIVED FROM CATHARANTHUS ROSEUS: Life Sciences-Microbiology - K. DHARMALINGAM; K.S. YOHA; M. K. YOGESWARI; R.S. SARANYA; P. SATHIYAROSINI; M. SUGANYA (International Journal of Life Science and Pharma Research, 2022)
In the present study, the methanolic leaf extract of Catharanthus roseus was extracted by soxhlet extraction process and the presence of alkaloid was detected using the thin layer chromatography. Further, the predominant compounds in the leaf extract were identified by GC-MS. The antibacterial activity of the extract was performed for various pathogenic bacteria such as Staphylococcus aureus, Eschericia coli, Bacillus megaterium, Bacillus subtilis, Bacillus flexus, Bacillus sp. SSKSD01 (KF751671), Bacillus sp. SSKSD05 (KF751673), Bacillus sp. SSKSD08 (KF751675), Pseudomonas sp. SSKSD06 (KF751674), Staphylococcus sp. SSKSD17 (KF751681), Klebseilla pneumoniae, Pseudomonas stutzeri, Pseudomonas fluorescens, Proteus vulgaris, Enterobacter aeruginosa by agar well diffusion method and the obtained results were compared with streptomycin as a positive control. From the present study, it was clear that the methanol extract of C. roseus leaf possessed antibacterial property.